AN ANALYSIS OF CHARACTER DEVELOPMENT IN A FANTASY NOVEL HOWL'S MOVING CASLTE - Mia Annisa Utami, - (2018)
The present study aims to examine the influence of magical events on the development of the major character in the novel Howl's Moving Castle by Diana Wynne Jones. The present study uses textual analysis approach. The data were collected by critically selecting the sentences and paragraphs that reflect events with magical happenings. In analyzing the data, this study employs Nikolajeva's (1988) magic laws. The analysis reveals that the magical events influence the development of the major character by generating the magic laws: consistency and limitation. Consistency binds the major character with the rules that restrict the major character to achieve her goal while limitation serves as a way for the major character to flee the rules and pursue her aspirations. The findings of the present study indicate that the fantasy world presented in the novel Howl's Moving Castle functions as recovery as the major character finds the betterment of herself through her journey in a magical world.